2020
DOI: 10.1111/aogs.14033
|View full text |Cite
|
Sign up to set email alerts
|

The tension‐free vaginal tape operation: Is the inexperienced surgeon a risk factor? Learning curve and Swedish quality reference

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A recent Swedish study showed that there is a learning curve, but the small effect size shows no clinical significance. The authors concluded that training new TVT surgeons will not expose patients to extra risks and will achieve the same results as the most experienced surgeon [41].…”
Section: Is Handling By the Surgeon Important?mentioning
confidence: 97%
“…A recent Swedish study showed that there is a learning curve, but the small effect size shows no clinical significance. The authors concluded that training new TVT surgeons will not expose patients to extra risks and will achieve the same results as the most experienced surgeon [41].…”
Section: Is Handling By the Surgeon Important?mentioning
confidence: 97%